The duality of violence and social tolerance and its effect on Andalusian poetry - Al-Samarrai, Prof. Dr. Ban Kazem Maki Al-Samarrai (Sulaimani Journal for Humanities, 2026)
The Duality of Violence and Social Tolerance in Andalusian Poetry (The Nasrid Era as a Model) Most heavenly religions share mechanisms of tolerance, forgiveness, and coexistence. These religions are characterized by religious values, morals, and spiritual integrity, which facilitates the process of promoting compassion and spreading the language of tolerance. Islam is tolerant, and its tolerance encompasses all aspects of life. Indeed, Islam calls for tolerance, even with the enemy and the opponent, in war, and in calling to it with wisdom and good preaching. As a result of studying the duality of violence and tolerance, the apparent is the behavior of tolerance, while violence is the implicit behavior. There is an inverse relationship between violence and tolerance, and this depends largely on the response, which contains within it the foundations of differentiation. The language of tolerance is the language desired and welcomed by humanity, and the duality of violence and tolerance is a natural phenomenon in human life, as it is used to express one's vision of the relationships existing between the components of existence. Talking about dualities means talking about the parallelism of dualities, especially the two extremes of violence and tolerance, side by side. The history of social violence begins with the emergence of contradictions in society. The classification of an act within society as violent is based on social norms and traditions. Social violence is expressed through apparent and tangible behaviors or practices that seek to change the social structure or declare the necessity or inevitability of changing it. Social tolerance is a recognition of the other on a human basis after stripping the reference to differentiation of racist values. Andalusian society was one of the societies that was distinguished by the diversity of races, religions, and customs. It included Arabs with their various tribes, and the subject of our research deals with rhythm and its effects in expressing violence and tolerance in the human soul, and how rhythm can have the ability to communicate and indicate.
Keywords: violence; tolerance; Andalusia; social; dualism